"Lumen": A Case Study on Domestic Violence - Ysmael, Fleoy (JPAIR Multidisciplinary Research, 2009)
A case study was done on"Lumen" a wife who is a victim of domestic violence with the husband as the perpetrator. Utilizing narrative analysis, findings, as supported by the propositions of Sociological Functionalist and Feminist Theories, revealed that "Lumen" has basically low self-esteem which later on became lowered due to the abuses; their family has a patriarchal system in which the husband dominates in decision-making and control of the family. She demonstrated an adaptation to the abusive condition as an effect to the repeated abuses, and has distorted decision-making ability. The inclusion of her children in the physical abuses of her husband led her to seek help at WCFC-VSMMC.
Keywords: Case study; domestic violence